ANALISIS LAJU PERTUMBUHAN DAN KONTRIBUSI PENERIMAAN PAJAK HOTEL DAN PAJAK RESTORAN TERHADAP PENDAPATAN PAJAK DAERAH (Studi pada Dinas Pendapatan Daerah Kota Malang) - Yuliani, Sofia Dwi (Jurnal Mahasiswa Perpajakan, 2015)
Malang city with all these consider Malang city as a city of travel, city of student, and city of industry which written on Tri Bina Cita Kota Malang. The position of Malang city can be seen from the amount of travel destination, education institution, and many kinds of industry which located in Malang city. This condition pulls the citizen outside Malang who come to Malang for living a while or stay in Malang. This things causes to the increase of hotel and restaurant services usage which increase the local tax income especially hotel and restaurant tax.This research include to kind of descriptive research with quantitative approach. This research located on Dinas Pendapatan Daerah Kota Malang. The purpose of this research is to describe the rate of growth and contribution of hotel and restaurant tax revenue and the efforts which done to increase the hotel and restaurant tax revenue. The result of this research shows that the average of growth rate of hotel and restaurant tax revenue in 2009-2013 reaches 25,73%, the growth rate of local tax income in 2009-2013 reaches 50,27%, and the average of contribution of hotel and restaurant tax revenue toward local tax income in 2009-2013 reaches 21,22% with sufficient criteria. The efforts which done by Dinas Pendapatan Daerah Kota Malang to increase the hotel and restaurant tax revenue through intensification and extensification and also applying online tax program. Keywords : Hotel Tax, Restaurant Tax, Local Tax, Rate of Growth, Contribution.